The Task Commitment on Student - Vanny Anggraini; Neviyarni S (Indonesian Institute for Counseling, Education and Theraphy, 2020)
Commitment to the task is interpreted as a responsibility, internal motivation that encourages someone to be diligent, tenacious, hard work, and practice that continues to do the task despite experiencing various obstacles or obstacles in doing the task. The purpose of this study was to find out how the students' commitment to the task. The scope of this study were students of Educational Administration in Padang State University in 2019, totaling 134 students. This research is a combination of Mixed Methods which combines two quantitative and qualitative methods. The summary of the results of this study is that students with Task Commitment in the very good category are 1 student with a percentage of 3.3%. students with Task Commitment 13 people in the good category with a percentage of 43.3%, then followed by 16 students whose Task Commitment is good with a percentage of 53.4%.